2018
DOI: 10.1111/liv.13745
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of muscle cramps to quality of life and sleep disturbance in patients with chronic liver diseases: A nationwide study

Abstract: Muscle cramps occurred with great frequency and were associated with various factors such as age, sex, hepatitis C virus and liver function. Many patients experience poor QOL (26.3%) due to muscle cramps, and therapeutic interventions are therefore needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 23 publications
(33 reference statements)
4
35
0
Order By: Relevance
“…Patients with CLD often describe sleep problems and the mechanisms of sleep disorders in such patients have not been fully investigated, however, they seem to be temporally linked to CLD itself [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. Sleep disorder, which involves difficulties in falling asleep, intermittent awakening during the night and shortened total sleep duration, is a burden and negatively affects the quality of life, mood changes, and possibly fatigue, and all of them can result in adverse consequences [ 19 , 20 ]. Sleep disorders can negatively affect the immune system and are commonly linked to neurocognitive disorders in patients with CLD, independently of liver fibrosis severity [ 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with CLD often describe sleep problems and the mechanisms of sleep disorders in such patients have not been fully investigated, however, they seem to be temporally linked to CLD itself [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. Sleep disorder, which involves difficulties in falling asleep, intermittent awakening during the night and shortened total sleep duration, is a burden and negatively affects the quality of life, mood changes, and possibly fatigue, and all of them can result in adverse consequences [ 19 , 20 ]. Sleep disorders can negatively affect the immune system and are commonly linked to neurocognitive disorders in patients with CLD, independently of liver fibrosis severity [ 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sleep is essential for mental and physical health and there is growing interest in sleep worldwide. Liver cirrhosis (LC) patients frequently describe sleep problems and non-LC patients with chronic liver diseases (CLDs) are not exceptions [1,2,3,4,5,6,7,8,9,10,11]. The mechanisms of sleep disturbance in CLD patients are not well elucidated; however, they appear temporally to be associated with CLD itself [12].…”
Section: Introductionmentioning
confidence: 99%
“…Some previous studies showed that the prevalence of sleep-wake disturbance was higher in LC patients than in controls (2,3,14). The causes of sleep-wake disturbance are related to hepatic encephalopathy, muscle cramps, melatonin metabolism disturbance, restless legs syndrome, and glucose level uctuation (2,3,(15)(16)(17)(18).…”
Section: Discussionmentioning
confidence: 97%
“…A large Japanese cohort study showed that muscle cramps in uence the sleep quality in 37.4% of patients with chronic liver disease (15). Nakanishi et al described that an 8-week L-carnitine treatment improved the muscle cramps of patients with LC (9).…”
Section: Discussionmentioning
confidence: 99%